Biological characteristics, biosafety prevention and control strategies for the 2022 multi-country outbreak of monkeypox - Chudan Liang; Jun Qian; Linna Liu (Elsevier, 2022)
Monkeypox is a zoonotic disease caused by the monkeypox virus (MPXV), which is a potential biological warfare agent of bioterrorism and poses the greatest threat to the world's public biosafety and health after variola virus (VARV). While the coronavirus disease 2019 (COVID-19) pandemic has not ended yet, monkeypox is spreading menacingly. The first case of monkeypox in a nonendemic country was confirmed on May 6th, 2022, while the first imported case from Asia was found on June 21st. There were more than 16 thousand reported cases as of July 23rd, the day the World Health Organization (WHO) declared the global monkeypox outbreak a public health emergency of international concern (PHEIC) at the same level as smallpox and COVID-19; while there were more than 53 thousand cases as of September 1st. Therefore, we will propose relevant biosafety prevention and control strategies after analyzing the etiology of the 2022 multi-country monkeypox outbreak from the biological feature, transmissibility, epidemic, and variability of MPXV.